Liver transplantation as a novel strategy for resolution of congenital afibrinogenemia in a pediatric patient. (6th October 2020) - Corrales‐Medina, Fernando F.; Miloh, Tamir; O'Farrell, Candelaria; Andrews, David M.; Tekin, Akin; De Angulo, Guillermo
Abstract: Fibrinogen replacement therapy is a treatment mainstay for patients with afibrinogenemia and significant bleeding. A male infant with congenital afibrinogenemia and several spontaneous hemarthroses commenced cryoprecipitate prophylaxis but developed severe urticarial reactions. He transitioned to a human fibrinogen concentrate (HFC) (RiaSTAP ®, CSL Behring; 70 mg/kg biweekly) but continued experiencing hemarthroses (estimated annualized bleeding rate [ABR]: 5‐6) and severe anaphylactic reactions, despite pre‐ and postinfusion medications. Following switching to a new HFC (Fibryga ®, Octapharma; 50 mg/kg biweekly), ABR was 0‐1 with no further infusion reactions. Aged 9 years, because of limited quality of life, development of obesity and fatty liver disease, he underwent orthotopic liver transplant (OLT) under HFC coverage. Pharmacokinetic analysis guided presurgical fibrinogen levels > 150 mg/dL. No intraoperative HFC infusions were required. Coagulation profile and fibrinogen levels remained within normal limits during and posttransplant. To our knowledge, this is the first pediatric report of afibrinogenemia successfully treated with OLT.